Compressive behaviour of aluminium rectangular hollow tube using Digital Image Correlation (DIC) method - Quanjin, Ma; Mohamad Nazirul Mubin, Merzuki; Rejab, M. R. M.; Noh, M. Z. C. (IOP Publishing, 2019)
The lightweight structural application is commonly used aluminium material, which generally applied in automotive, military, aerospace and naval applications. The rectangular cross-section hollow tube of aluminium material performs the better compressive properties compared to other cross-section shapes. In order to investigate the compressive behaviour of aluminium tube, Digital Image Correlation (DIC) method is used to study the evolution of deformation and strain value. The quasi-static compressive test was performed, and the experimental result was compared with the DIC measurement results. It was obtained that the failure behaviour of the aluminium rectangular hollow tube was buckling mode with several inwards and outwards deformation. In addition, it was concluded that the DIC method results were lower than the experimental values on the maximum compressive stress and compressive modulus, which was considered as a good agreement between this two methods with 1.7 % percentage of error. It is suggested that DIC method is a sufficient method to measure the deformation and strain values with non-contact and non-destructive features.